Shocks to Bank Lending, Risk-Taking, Securitization, and their Role for U.S. Business Cycle Fluctuations - Gert Peersman; Wolf Wagner (Center for Economic Studies and ifo Institute (CESifo), 2014)
Shocks to bank lending, risk-taking and securitization activities that are orthogonal to real economy and monetary policy innovations account for more than 30 percent of U.S. output variation. The dynamic effects, however, depend on the type of shock. Expansionary securitization shocks lead to a permanent rise in real GDP and a fall in inflation. Bank lending and risk-taking shocks, in contrast, have only a temporary effect on real GDP and tend to lead to a (moderate) rise in the price level. Furthermore, there is evidence for a strong search-for-yield effect on the side of investors in the transmission mechanism of monetary policy. These effects are estimated with a structural VAR model, where the shocks are identified using a model of bank risk-taking and securitization.
Keywords: C32; E30; E44; E51; E52; 330; bank lending; risk-taking; securitization; SVARs